2017
DOI: 10.1111/sode.12246
|View full text |Cite
|
Sign up to set email alerts
|

Pet dogs: Does their presence influence preadolescents' emotional responses to a social stressor?

Abstract: Despite interest in human-animal interaction, few studies have tested whether the presence of a dog facilitates children's emotional responding. Preadolescents (N 5 99) were randomly assigned to complete the Trier Social Stress Test either with or without their pet dog.Children rated their positive and negative affect, and high-frequency heart rate variability (HF-HRV) was assessed throughout the session.Children reported higher positive affect when they completed the task with their pet dog, although there we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Both in riders and dog owners self-reported mood ratings during/after the activity correlated with their pet attachment [63], which was in accordance with other studies [20,97]. They feel positive emotions [97] and happiness [20].…”
Section: Pet Attachmentsupporting
confidence: 89%
“…Both in riders and dog owners self-reported mood ratings during/after the activity correlated with their pet attachment [63], which was in accordance with other studies [20,97]. They feel positive emotions [97] and happiness [20].…”
Section: Pet Attachmentsupporting
confidence: 89%
“…Similarly to loneliness, the reduction occurred rapidly within 3 months and persisted until the end of the study. The mood enhancing effects of acute human–dog interactions, detailed above, may improve chronic measures of affect through the occurrence of regular acute human–dog interactions as seen in dog ownership [31, 32, 65]. We also observed a reduction in negative affect in the lagged control group, albeit to a lesser extent than the dog acquisition group, which may be the result of study participation effects [78], as described above.…”
Section: Discussionmentioning
confidence: 60%
“…A possible explanation for our findings is that human–dog interactions elicit acute positive effects on mood [31, 32, 65], and the regular occurrence of these interactions, as seen in dog ownership, produces long-term improvements. Indeed, research investigating the efficacy of canine interactions in reducing psychological distress in university students [31, 32] and preadolescents [65] has found brief human–dog interactions can acutely improve positive affect and reduce negative affect. Considering the association between loneliness and negative mood [66], it is plausible that the potential mood enhancing effects of regular human–dog interactions may reduce loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that short-term, unstructured interactions with a therapy dog can significantly reduce self-reported anxiety and distress levels [e.g., ( 18 )]. For example, children with their pet dog or a therapy dog present during a stressful task exhibit lower perceived stress and more positive affect compared to when alone ( 19 ), when a parent was present ( 20 ), or when a stuffed dog was present ( 21 ). In addition to psychological mechanisms, there are social and biological mechanisms at play as well.…”
Section: Theoretical Framework For Dog Interaction Benefitsmentioning
confidence: 99%